BDNF Genotype Interacts with Motor Function to Influence Rehabilitation Responsiveness Poststroke - Shiner, Christine T.; Pierce, Kerrie D.; Thompson-Butel, Angelica G.; Trinh, Terry; Schofield, Peter R.; McNulty, Penelope A. (Frontiers in Neurology, 2016)
Background. Persistent motor impairment is common but highly heterogeneous post-stroke. Genetic polymorphisms, including those identified on the brain derived neurotrophic factor (BDNF) and apolipoprotein E (APOE) genes, may contribute to this variability by limiting the capacity for use-dependent neuroplasticity, and hence rehabilitation responsiveness. Objective. To determine whether BDNF and APOE genotypes influence motor improvement facilitated by post-stroke upper-limb rehabilitation. Methods. BDNF Val66Met and APOE isoform genotypes were determined using leukocyte DNA for 55 community-dwelling patients 2-123 months post-stroke. All patients completed a dose-matched upper-limb rehabilitation program of either Wii-based Movement Therapy or Constraint-induced Movement Therapy. Upper-limb motor-function was assessed pre- and post-therapy using a suite of functional measures. Results. Motor-function improved for all patients post-therapy, with no difference between therapy groups. In the pooled data, there was no significant effect of BDNF or APOE genotype on motor-function at baseline, or following the intervention. However, a significant interaction between the level of residual motor-function and BDNF genotype was identified (p=0.029), whereby post-therapy improvement was significantly less for Met allele carriers with moderate and high, but not low motor-function. There was no significant association between APOE genotype and therapy outcomes. Conclusions. This study identified a novel interaction between the BDNF Val66Met polymorphism, motor-function status and the magnitude of improvement with rehabilitation in chronic stroke. This polymorphism does not preclude, but may reduce, the magnitude of motor improvement with therapy, particularly for patients with higher but not lower residual motor-function. BDNF genotype should be considered in the design and interpretation of clinical trials.